Pengaruh Edukasi Kesehatan terhadap Pengetahuan Siswa tentang Bahaya Obesitas di MTsN Bintan - Nanin Juliana; Iwan Kurniawan; Yelnawati Yelnawati (Public Health Journal, 2026)
Adolescent obesity is a health issue that increases the risk of chronic diseases. It can arise from various factors, including genetic and environmental causes, making it essential to provide information regarding the factors that contribute to obesity. This study aimed to determine the effect of health education on students' knowledge concerning the dangers of obesity. A pre-experimental, one-group pre-test and post-test design was employed, involving a sample of 36 ninth-grade students selected via proportional sampling. The results indicated that prior to the education, 77% of students had a low level of knowledge; following the education, 83.3% demonstrated good knowledge, while 16.7% showed adequate knowledge. The Wilcoxon test yielded Z = 4.904; p < 0.001, indicating a significant effect of health education on improving students' knowledge. Conclusion: health education is effective in enhancing students' knowledge regarding the dangers of obesity.